Quantification of viable bioaerosol emanation from an ACMV system and its impact on indoor bioaerosol pollution - Xiong, Jin Wen (2021)
Viable bioaerosol can deposit and multiply in air-conditioning and mechanical ventilation (ACMV) systems, eventually entering indoor environments after these systems are operated and contributing to indoor pollution. We propose a method for identifying and quantifying the emanation of viable bioaerosol from an ACMV system and its impact on indoor pollution through surface and air sampling followed by analysis using a material-balance model. Adopting this method, we investigated the contribution of viable bioaerosol from an ACMV system to the indoor pollution in an air-conditioned room located in Singapore. The system, which emanated viable bacteria and viable fungi at the rates of 2.4 CFU s–1 and 3.9 CFU s–1, respectively, was the largest source of indoor viable bacteria and the second largest source of indoor viable fungi (exceeded only by the outdoor fungi introduced through mechanical ventilation) in the air. Potentially pathogenic bioaerosol species in the genera of Staphylococcus, Moraxella and Aspergillus were also identified in the ACMV system. In particular, Moraxella osloensis, the most likely genus to originate from occupants, was found to accumulate in the ACMV system, indicating the potential effect of this system’s cleanliness on indoor pollution. Our method can be used as a tool for analysing the potential sources of indoor bioaerosol and supporting the development of effective control measures for bioaerosol emanation from ACMV systems.